Proceedings of the 2018 International Conference on Industrial Enterprise and System Engineering (IcoIESE 2018) 2019
DOI: 10.2991/icoiese-18.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence An Academic Institution's Intention To Accept CloudIOT: A Proposed Framework

Abstract: The combination of Cloud Computing (CC) and Internet of things (IOT) which is known as CloudIOT are two different kinds of technologies that are already part of our lives. The growing usage of CloudIOT in the education sector is changing the Teaching and Learning processes. There is very limited study related to the factors which effect students' acceptance of CloudIOT innovations in an academic institution. The aim of this paper is to illustrate different aspects of CloudIOT and to understand the beneficial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…To obtain the model fit of the conceptual model, AMOS software version 28 is used, and results are generated. [5]- [8], [23]- [27] Table 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the model fit of the conceptual model, AMOS software version 28 is used, and results are generated. [5]- [8], [23]- [27] Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the researchers [19]- [25] identified that information security influences cloud computing adoption. Behavioural Intention is the strong mediating factor identified by many research [5]- [8], [23]- [27] that mediate the adoption of cloud computing with all independent variables. Table 1 summarises the adoption frameworks or models that relate the significant factors that influence cloud computing adoption with the recent references.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, findings were derived from the study of Karahoca et al (2018) who found that privacy affected the intention to use IoT. Ireda et al (2019) hypothesized that concerns around privacy would have a major impact on the UB of cloud-based IoT. On the other side, Hsu and Lin (2018) discovered that the presence of privacy has a detrimental impact on the value that is perceived.…”
Section: Privacy and Adoption Of Iotmentioning
confidence: 98%
“…Sepasgozar et al (2018) discovered that mobile security has no impact on PEOU. Ireda et al (2019) hypothesized that security would have a beneficial impact on cloud IoT adoption. Al-Hashimy et al ( 2019) discovered that security positively influenced IoT adoption.…”
Section: Security and Adoption Of Iotmentioning
confidence: 99%
“…TOE is different from other theoretical adoption models and frameworks because it includes the variables that are related to technology, organization, and environment [36]. The TOE includes technological related factors that are more related to the characteristics such as the security, trust, and risk of involving in technological transaction [37] [38], [39]. The organizational factors based on TOE includes factors that are related to the characteristic of the organization such as the age and the size.…”
Section: Theoretical Frameworkmentioning
confidence: 99%